Image Segmentation and Text Extraction Techniques for Efficient Information Retrieval - Wydyanto, .; Ade, Putra; Maria, Ulfa (INTI International University, 2025)
Image segmentation and text extraction are important tasks in the field of computer vision and image processing. Image segmentation and text extraction involve identifying and separating objects or regions within an image, and helping visually impaired individuals access visual content. The ability to accurately extract text from scene images can have various applications and benefits. This can help automatically generate captions or descriptions for images, making them more accessible to individuals with visual impairments. This can help in tasks such as indexing and image search, where the extracted text can be used to improve the accuracy and relevance of search results. In addition, the extracted text can be used for sentiment analysis or other forms of text-based analysis, providing valuable insights into the content and context of the images. As the techniques discussed in the paper have the potential to help enhance the utility and usability of scene images in various applications and domains.